(untitled) (American Journal of Islam and Society, 2011)
Holy places have frequently been the focus of religious and political conflict. Ron E. Hassner analyzes the causes, the course, and the outcomes of such conflicts. His prologue, “A Terrifying and Fascinating Mystery,” is an account of his visit to Jerusalem’s Old City, which the three revealed faiths share. The reader is made acquainted with the city’s human and linguistic diversity, the narrow alleys, the smells of the bazaar, the monumental buildings, the security checks, and the risks and hardships that visitors may face. The first of the book’s nine chapters is an introduction. The remaining eight are divided into two parts: part 1 is “Understanding Conflicts over Sacred Spaces,” while part 2 deals with “Managing Conflicts over Sacred Spaces.” Each part consists of four chapters. Photographs are mostly placed between the chapters. The book ends with acknowledgments, followed by notes with references and clarifications, and an index of terms, people, and places ...